The Principal's Leadership Strategy in Building Religious Character Thru Morning Imtaq - M. Junaidi (Journal of Practice Learning and Educational Development, 2025)
This research aims to analyze the principal's leadership strategies in developing students' religious character and discipline at SMK Yapis Santong. This study is motivated by a unique school policy that requires students to arrive at 06.15 AM to participate in a 60-minute morning Imtaq (Faith and Piety) program. Using a qualitative approach with a case study design, data were collected through in-depth interviews with the principal, teachers, and students, as well as participatory observation and documentation. The results indicate that the principal's leadership strategy is implemented through three integrated stages: (1) Environmental engineering by setting early arrival times to encourage students to wake up early and perform Subuh prayers; (2) Spiritual strengthening through the collective recitation of the Al-Qur'an and Asmaul Husna; and (3) Soft skill development through public speaking practice (muhadharah). The findings reveal that this consistent leadership approach effectively fosters student discipline and mental readiness before formal classes begin at 07.15 AM. This study concludes that the principal's commitment to being a role model is the key factor in the successful internalisation of religious values and work ethics in a vocational school environment.